Penerapan Metode Technometrik Untuk Penilaian Kapabilitas Teknologi Industri Galangan Kapal Dalam Menyongsong Era Industri 4.0 - Utomo, Satrio; Setiastuti, Nugraheni (STIKOM Tunas Bangsa Pematangsiantar, 2019)
The national shipyard industry is one of the strategic and competitive industries that deserve to be developed. The current developing era, namely the industrial 4.0, the growth of the national shipyard industry is expected to be able to active in the era of industry 4.0. In certain aspects and scales, the capabilities possessed are not inferior to world-class capabilities, but further development is still needed, referring to the fact that many domestik fleet needs and repairs are still dependent on foreign shipyards. So far, the domestic shipyard industry still facing a number of challenges, including financial support from the financial sector. Therefore measurement is needed toincrease rationalization towards labor productivity. The objective of reseach was first, identify and evaluate the operation of the current national shipyard industry by assessing the level of shipyard technology. Second, to know the strengths and weakness of technology so that management can know which technology development priorities must first be given attention andimprovement an effort to meet the industrial 4.0. The technology capability level can be determined based on the TCC (Technology Contribution Coefficient) which is a Technometrics method developed by UN-ESCAP. Based on the results of the assessment is the level of shipyard technology of PT. DOK Kodja Bahari based on Technoware, Humanware, Infoware, and Orgaware components is 0.519 which shows a good classification at the level of semi-modern technology.